Geometric Problem Solving Skill Analysis of Primary School Learners Taught by Module Assisted Independent PBL Model - Faujiyah, Siti; Sukestiyarno, YL; Kharisudin, Iqbal (Educational Management, 2021)
The underlying background of this research was the importance of teaching problem solving skill as 21st-century skills. Providing a qualified learning facility to train learners solving problems is a challenge for teachers. This research applied the Problem Based Learning model as innovative learning in the form of independent learning. The learners did this independent learning with the given geometric problem solving module. The teachers guided the learning process via online. It was also monitored by the learners' parents as well as the peer tutors. After the lesson, an evaluation and a work discussion were promoted together with the school teachers. This research examined the learning quality taught by module-assisted independent PBL model. It consisted of analyzing the learning instrument validity level, the learning implementation, and the model effectiveness as indicated by the completeness and the correlation tests. This research applied a mixed method with sequential exploratory design. The finding showed the learning instrument was valid. Thus, it could be applied practically at school. The effectiveness level showed that PBL model based on independent learning and assisted by module was effective. The completeness test results, assisted by SPSS, showed Sig score higher than 5%, 0.731. Thus, it had reached the completeness. The correlation test assisted by SPSS obtained a sig score of 0.3%. It was lesser than 5%. Thus, there was a correlation between learning autonomy toward problem solving skills. Therefore, this module-assisted independent PBL model was qualified based on the plan, the implementation, and the evaluation. Thus, it could be a qualified learning alternative at primary school.